A comprehensive strategy for the subtyping of patients with Fanconi anaemia: conclusions from the Spanish Fanconi Anemia Research Network. Issue 4 (14th November 2006) - Antonio Casado, José; Callén, Elsa; Jacome, Ariana; Río, Paula; Castella, Maria; Lobitz, Stephan; Ferro, Teresa; Muñoz, Arturo; Sevilla, Julián; Cantalejo, Ángeles; Cela, Elena; Cervera, José; et al.
Abstract : Background: Fanconi anaemia is a heterogeneous genetic disease, where 12 complementation groups have been already described. Identifying the complementation group in patients with Fanconi anaemia constitutes a direct procedure to confirm the diagnosis of the disease and is required for the recruitment of these patients in gene therapy trials. Objective: To determine the subtype of Fanconi anaemia patients in Spain, a Mediterranean country with a relatively high population (23%) of Fanconi anaemia patients belonging to the gypsy race. Methods: Most patients could be subtyped by retroviral complementation approaches in peripheral blood T cells, although some mosaic patients were subtyped in cultured skin fibroblasts. Other approaches, mainly based on western blot analysis and generation of nuclear RAD51 and FANCJ foci, were required for the subtyping of a minor number of patients. Results and conclusions: From a total of 125 patients included in the Registry of Fanconi Anaemia, samples from 102 patients were available for subtyping analyses. In 89 cases the subtype could be determined and in 8 cases exclusions of common complementation groups were made. Compared with other international studies, a skewed distribution of complementation groups was observed in Spain, where 80% of the families belonged to the Fanconi anaemia group A (FA-A) complementation group. The high proportion of gypsy patients, all of them FA-A, and the absence of patients with FA-C account for this characteristic distribution of complementation groups.